EXPLORING EFL STUDENTS’ PERSPECTIVE IN IMPROVING THEIR ENGLISH PRODUCTIVE SKILLS: EXISTING COMPETENCIES AND ENCOUNTERED CHALLENGES - Aisyah, Sri; Rasyid, Muhammad Nur Akbar; Nasrum; Djamereng, Jumharia; Asnur, Sardian Maharani (UIN Alauddin Makassar, 2024)
ABSTRACT This research is focused on the fundamental competencies of students majoring in English and Literature, with the objective of identifying and evaluating their productive language skills and addressing the challenges they encounter in enhancing speaking and writing skills.Quantitative analysis serves as the methodology for this study. The analysis of the data reveals two key findings. Firstly, there exists a diversity of proficiency levels among students, predominantly at the intermediate level. Notably, writing proficiency remains a challenge, with only 53% of students averaging between 1-4 on the scale, indicating a lack of mastery. Similarly, when it comes to writing skills, 60% of students fall within the range of 1 to 4 on the scale. Secondly, challenges stem from various factors, including limited exposure to English outside the classroom, difficulties in grasping cultural context, and a lack of confidence in public speaking. Proposed solutions include the incorporation of interactive learning methodologies, provision of supplementary speaking sessions, and the promotion of cultural sensitivity through diverse activities.